Considerations and procedures for the successful introduction of farm mechanization - Davies, Cornelius (Rome, Italy : Food and Agricultural Organisation of the United Nations, 1954)
It is the purpose of this paper to outline and emphasize what must be considered and provided to be reasonably sue that power machinery will lead to an improvement of agriculture.
osc 15/04/2019
Loans
Keywords: Agriculture; Farm mechanisation